PKM PENDAMPINGAN PEMBUATAN ABON KULIT PISANG DI KABUPATEN TULUNGAGUNG - Siti Napfiah; Asri Putri Anugraini; Farizha Irmawati (JPM PAMBUDI, 2018)
Program society partnership is training abon's makings banana skin at Regency Tulungagung aims to give science and training makes a new innovation product namely abon banana skin in order to develop Regency citizen effort Tulungagung that not only utilize its banana only. At chooses two flaky producer partners bananas at Regency Tulungagung to been given training abon's makings that gets banana skin raw product. Two elected partner gets location at Kauman and Boyolangu. Two this effort partner did not utilize its banana skin eventually well-nigh every day making banana so banana skin flaky piles. By this program, given by science newing to that society banana skin can be utilized as a product that valuably namely abon banana skin. Reasonable banana skin to be made food product because banana skin has goodly nutrient content lovely. Abon reasonably to been kept up because top abon that than so long without bahna preservative and is liked by all society circle. Society devotion program this executed beginning month of February 2018. Via test-driving activity sort recipe and discussion with partner therefore at finds recipe to make abon banana skin who can get long-lasting, having a real treat, pretty color, and texture that nicely corresponds to banana skin type that is at partner effort place. Activity on programs it to get positive comment of Tulungagung's Regency citizen. They really enjoy following this activity.